Il soggetto della narrazione psichiatrica - Praino, Evelina (B@belonline, 2020)
In this text I develop a new reflection about the relation between madness and therapy. According with the tradition ofthe phenomenological psychiatry and the studies of Michel Foucault, I will discuss the account of madness presupposed by a number of psychiatric theories from the 20th century onwards. I will deal with these theories through the particular conceptual tool of narration. Indeed, no psychiatric approach can elude a serious confrontation with the patient’s existential narration, for two reasons. First, there is no psychiatric investigation outside the hermeneutics of the subject’s lived-experience. Secondly, the written or narrated word, by producing subjectivities, allow for a combination of the existential experience of the healthy individual with the insane. Lastly, accounting for madness as an object recently constituted as a disease and codified by a science that, as a rational framework, remains totally alien from it, clarifies that the discourse on madness is the partial and external report of a lived-experience never compared to self-narration. Thus, madness still upsets our subjectivity about its relation to the world and the other precisely because there has never been a discourse on the concrete possibility of a radical incommunicability between madness and reason. Perhaps, such an incommunicability should be only exhibited.